MODAL SOSIAL KEMITRAAN KELOMPOK PETANI DI KAWASAN HUTAN RARUNG SELAMA PANDEMI COVID-19 - Pande Komang Suparyana; Addinul Yakin; Amiruddin Amiruddin; Halimatus Sa’diyah; L. Sukardi (Lambung Mangkurat University-Indonesia, 2022)
Community participation in agroforestry activities is influenced by various internal factors of farmers, aspects of extension performance, and group social system support. So that social capital becomes the glue for each individual, in the form of norms, trust and networks, so that mutually beneficial cooperation occurs, to achieve common goals. The purpose of this study was to analyze the role of social capital in the partnership of farmer groups in the Rarung forest area during the Covid-19 pandemic. Respondents were taken as many as 52 farmers who are in the Rarung Forest Area, especially Pemepek Village, Pringgarata. Social capital analysis uses descriptive analysis using a Likert scale. The results showed that the role of social capital was very good in the Partnership of Farmer Groups in the Rarung Forest Area during the Covid-19 Pandemic in Pemepek Village, Pringgarata District, Central Lombok Regency, West Nusa Tenggara Province. The social capital component is focused on trust, social networks, social norms, proactive actions and reciprocity with a value of 85.93% which indicates the high role of social capital (trust, social networks, social norms, proactive actions and resiprocity) Partnership of Farmer Groups in the Rarung Forest Area During the Covid-19 Pandemic. Trust, social networks, social norms, proactive actions and reciprocity of group members carry out life in high social capital both within the group and in communities outside the group to strengthen ties of brotherhood, tolerance, and as an effort to make the business run well.